Observation of the Low‐Frequency Spectrum of the Water Dimer as a Sensitive Test of the Water Dimer Potential and Dipole Moment Surfaces. (15th August 2019) - Schwan, Raffael; Qu, Chen; Mani, Devendra; Pal, Nitish; van der Meer, Lex; Redlich, Britta; Leforestier, Claude; Bowman, Joel M.; Schwaab, Gerhard; Havenith, Martina
Abstract: Using the helium nanodroplet isolation setup at the ultrabright free‐electron laser source FELIX in Nijmegen (BoHeNDI@FELIX), the intermolecular modes of water dimer in the frequency region from 70 to 550 cm −1 were recorded. Observed bands were assigned to donor torsion, acceptor wag, acceptor twist, intermolecular stretch, donor torsion overtone, and in‐plane and out‐of‐plane librational modes. This experimental data set provides a sensitive test for state‐of‐the‐art water potentials and dipole moment surfaces. Theoretical calculations of the IR spectrum are presented using high‐level quantum and approximate quasiclassical molecular dynamics approaches. These calculations use the full‐dimensional ab initio WHHB potential and dipole moment surfaces. Based on the experimental data, a considerable increase of the acceptor switch and a bifurcation tunneling splitting in the librational mode is deduced, which is a consequence of the effective decrease in the tunneling barrier. Abstract : Die intermolekularen Moden des Wasserdimers wurden im Frequenzbereich von 70 bis 550 cm −1 aufgenommen und konnten Donortorsion (inkl. Oberton), Akzeptor‐Wagging und ‐Twisting, intermolekularem Strecken und In‐plane‐ sowie Out‐of‐plane‐Schwingungsmoden zugeordnet werden. Die Daten liefern einen Benchmark für Wasser‐Potentialflächen und Dipolmomente. Berechnungen des IR‐Spektrums wurden mittels Molekulardynamik‐Ansätzen durchgeführt.